2019
DOI: 10.1089/neu.2019.6376
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Administration of Angiotensin-(1-7) Improves Recovery after Traumatic Brain Injury in Mice

Abstract: Angiotensin II (Ang II)-mediated activation of its type I receptor (AT1R) in the central nervous system promotes glial proliferation, local inflammation, and a decrease of cerebral blood flow. Angiotensin-(1-7) (Ang-(1-7))-an Ang II derivative peptide-signals through the Mas receptor (MasR) in opposition to Ang II/AT1R, promoting anti-inflammatory, vasodilatory, and neuroprotective effects. As our laboratory has previously demonstrated beneficial effects of AT1R inhibition following controlled cortical impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
4
27
0
Order By: Relevance
“…Aside from cardiovascular regulation however, Ang-(1–7) and Mas receptor signalling have demonstrated specific effects on brain cells such as: reduced nuclear and mitochondrial superoxide production [ 147 ]; improved neuronal survival and reduced oxidative stress in the brain mediated via PKA [ 148 ], or improved survival and reduced levels of ROS in rotenone induced injury of cultured neurons mediated by increased antioxidant activity and reduced NOX activity [ 149 ]; reduced microglial activation and astrogliosis allowing for improved neuronal density following traumatic brain injury [ 150 ]; reduced inflammation in astrocytes mediated by the MAPK inhibition signalling pathway [ 151 ]; reduced Shiga toxin 2 (Stx2) induced neuronal, astrocyte and oligodendrocyte damage [ 152 ]; or a switch to the anti-inflammatory M2 microglia phenotype with a reduction in pro-inflammatory cytokines (TNFα and IL1β) and increased levels of anti-inflammatory IL-10 [ 153 ]. Moreover, central Ang-(1–7) administration has demonstrated an increase in bradykinin levels and expression of bradykinin receptors [ 154 ] which may itself have neuroprotective effects [ 155 ]; or protection against cerebral endothelial cell dysfunction and oxidative stress via NOX inhibition and the PI3K/NO signalling pathway [ 156 ].…”
Section: Ras Receptor Signallingmentioning
confidence: 99%
“…Aside from cardiovascular regulation however, Ang-(1–7) and Mas receptor signalling have demonstrated specific effects on brain cells such as: reduced nuclear and mitochondrial superoxide production [ 147 ]; improved neuronal survival and reduced oxidative stress in the brain mediated via PKA [ 148 ], or improved survival and reduced levels of ROS in rotenone induced injury of cultured neurons mediated by increased antioxidant activity and reduced NOX activity [ 149 ]; reduced microglial activation and astrogliosis allowing for improved neuronal density following traumatic brain injury [ 150 ]; reduced inflammation in astrocytes mediated by the MAPK inhibition signalling pathway [ 151 ]; reduced Shiga toxin 2 (Stx2) induced neuronal, astrocyte and oligodendrocyte damage [ 152 ]; or a switch to the anti-inflammatory M2 microglia phenotype with a reduction in pro-inflammatory cytokines (TNFα and IL1β) and increased levels of anti-inflammatory IL-10 [ 153 ]. Moreover, central Ang-(1–7) administration has demonstrated an increase in bradykinin levels and expression of bradykinin receptors [ 154 ] which may itself have neuroprotective effects [ 155 ]; or protection against cerebral endothelial cell dysfunction and oxidative stress via NOX inhibition and the PI3K/NO signalling pathway [ 156 ].…”
Section: Ras Receptor Signallingmentioning
confidence: 99%
“…Angiotensin I is an inactive peptide, serving as a precursor for bioactive angiotensins. Cleavage of angiotensin I by Nln results in angiotensin-(1–7), which was shown to have neuroprotective and anti-inflammatory effects in in vivo stroke and TBI models [33,34]. Complementary to this, Nln inactivates angiotensin II, which is the most studied peptide in the renin-angiotensin system with mounting evidence supporting its pathological role in stroke and TBI [35,36].…”
Section: Nln Substrates and Their Role In Acute Neurodegenerationmentioning
confidence: 99%
“…Angiotensin I is an inactive peptide, serving as a precursor for bioactive angiotensins. Cleavage of angiotensin I by Nln results in angiotensin-(1-7), which was shown to have neuroprotective and anti-inflammatory effects in in vivo stroke and TBI models [33,34].…”
Section: Nln Substrates and Their Role In Acute Neurodegenerationmentioning
confidence: 99%
“…As candesartan has been shown to induce activity and expression of ACE2, the enzyme that converts Ang II to the Mas receptor ligand, Ang-(1-7), it has been postulated that some of candesartan's beneficial effects may be mediated by enhancing activation of the ACE2/Ang-(1-7)/MasR axis (Pernomian et al, 2015). Indeed, we have previously shown that Ang-(1-7) treatment after TBI can also enhance recovery (Janatpour et al, 2019). Further delineation of which receptor mediates candesartan's regulation of gene expression will await experiments involving specific receptor knockout mice.…”
Section: Discussionmentioning
confidence: 98%